Economics and Management of Freshwater Prawn Culture in Western Hemisphere - Valenti, Wagner C. [UNESP]; Tidwell, James H. (Wiley, 2007)
Freshwater prawn farming is currently one of the fastest growing sectors of aquaculture mainly due to the remarkable developments in culture technologies and their greater environmental sustainability compared to penaeids. Currently, it is possible to produce 2.5 t/ha/crop in temperate regions and more than 6 t/ha/year of 40 g prawns in tropical areas. Production strategies are site-specific and vary in the temperate, subtropical, and tropical regions. The main opportunities for industry development in Americas and Caribbean are the availability of modern production technologies, inexpensive labor and land in several areas, and large local markets. The main constraints is the scanty structure of the productive chain. Internal rates of return from 20% to 45% and payback from 3 to 5 years for grow-out phase are feasible. The productive chain, production strategies, and costs, as well as selling prices and economic indicators, of freshwater prawns culture in the western hemisphere are described and discussed. © 2006 Blackwell Publishing.
Keywords: Economics; Freshwater prawn; Macrobrachium; Productive chain